OCP Oracle database 11g administrator certified professional study guide - Freeman, Robert G. 1965- (Wiley, 2009)
This updated study guide for the latest release of the most popular database software in the world--Oracle Database 11 g -- reviews using the RMAN recovery catalog, handling Flashback technology, managing memory and resources, automating tasks, diagnosing the database, and much more. Plus, more than 100 pages of workbook exercises help prepare you to take the 1Z0-053 exam. Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.
"Exam 1Z0-053"--Cover. - CD-ROM contains text of book in .pdf format plus additional materials. - Includes index. - Print version record
Keywords: Oracle (Computer file) -- Study guides -- Examinations; Database management -- Study guides -- Examinations; Oracle (Computer file) / Examinations / Study guides; Oracle (Computer file); Bases de données; Gestion; Examens; Guides de l'étudiant; COMPUTERS; Data Processing; Database management; Examinations; Study guides; Database management; Examinations; Examinations; examination study guides; Study guides; Guides de l'étudiant